Prospects of implementation and practice compliance with marketing standards in Ukraine and the EU - Zhaldak, G.; Shulgina, L. (Видавництво Львівської політехніки, 2016)
In the presented article the prospects for implementing marketing standards in Ukraine and the EU are examined. Investigated the practice compliance with such standards in our country and the EU. Systematized approach to standardization and the main prospects for further integration into the European space. It is determined, that implementing marketing standards in the practice of domestic enterprises is connected with the necessity of forming the country's favorable conditions for participation in international cooperation, access to international markets, and cooperation with foreign investors. Implementing marketing standards in Ukraine and the EU are examined. To standardizing mostly belong high-tech products and related products such as cars, computers, audio and video equipment, etc., as well as products from the category of luxury, focused on the emotional and imaginative perception (perfume, clothes, jewelry). In addition, standardized strategies and advertising campaigns are more effective when the product has a utilitarian purpose and advertising information or the attractive features of the product closely associated with the national peculiarities. A procedure for transition to EU marketing standards is suggested, taking into account the fact that marketing standards do not affect the regulatory process technology and production techniques, they are different in different countries, corresponding to national standards. They regulate only the basic, fundamental aspects that affect the formation of the marketing policy of the company, displaying the results of marketing and communication policy of the company. Based on the new understanding of the role and place of standardization in the marketing activities and successful implementation of EU standards by creating appropriate institutional environment, the attention is accented on marketing standards which may be an important factor in the formation of a market economy model, contribute to the achievement of sustainability development and establishment of equivalent relations between the trading partners in the common market. The algorithm of formatting a model of EU marketing standards in Ukraine is suggested, taking into account the introduction of the practice of marketing standards in EU. The potential barriers to the implementation of EU marketing standards in Ukraine, which are presented as a SWOT-analysis of standardization policy in terms of its adaptation to the EU are analyzed. In conclusion the main directions of implementation of international standards (create an international image of the product, reducing development costs and production of advertising, accelerating simultaneous entering the markets of different countries, improving the efficiency of voice as the benefits of a product or service are equally perceived in any country and supported by identical positioning) are indicated and is determined that the use of marketing standards – is a kind of tactical tool for promoting products to overseas markets and is seen as the willingness of the state to reform and integration into the world economic community. Впровадження маркетингових стандартів у практику діяльності вітчизняних підприємств пов’язано із необхідністю формування у країні сприятливих умов для участі у міжнародній співпраці, виходу на міжнародні ринки, співпраці з іноземними інвесторами. Розглянуто особливості впровадження маркетингових стандартів в Україні та ЄС. Досліджено практику дотримання таких стандартів у нашій державі та країнах Євросоюзу. Систематизовано підходи до стандартизації та визначено основні перспективи подальшої інтеграції нашої країни у європейський простір. На основі вивчення практики впровадження маркетингових стандартів у ЄС запропоновано алгоритм формування моделі розвитку маркетингових стандартів ЄС в Україні.
Перспективи реалізації і практика дотримання маркетингових стандартів в Україні та ЄС
Keywords: marketing standards; European Union; integration; practice compliance with standards; implementation; маркетингові стандарти; Європейський Союз; інтеграція; практика дотримання стандартів; іпмплементація